Selenite supplementation reduces arsenate uptake greater than phosphate but compromises the phosphate level and physiological performance in hydroponically grown Oryza sativa L. . (3rd December 2015) - Kumar, Navin; Dubey, Arvind Kumar; Jaiswal, Praveen Kumar; Sahu, Nayan; Behera, Soumit Kumar; Tripathi, Rudra Deo; Mallick, Shekhar
Abstract: The present study evaluates the reduction of arsenate (As[V]) uptake in rice seedlings through individual and combined supplementation of phosphate (PO4 3– ) and selenite (Se[IV]) in a hydroponic condition. The toxic response in seedlings receiving As(V) manifested as inhibition in physiological parameters such as water use efficiency, stomatal conductance, photosynthetic assimilation rate, transpiration rate, photochemical quenching, and electron transport rate, along with growth. Arsenic accumulation significantly decreased with Se(IV) treatment (0.5 μg mL −1, 1 μg mL −1, and 2 μg mL −1 ) in a dose‐dependent manner (20%, 35%, and 53%, respectively); however, it compromised the PO4 3– level and physiological performance. The lower level of Se(IV), (0.5 μg mL −1 ), was relatively beneficial in terms of reduction in As accumulation than the higher level of Se(IV), (2 μg mL −1 ), which was rather toxic. Further, decrease in As uptake, replenished the level of PO4 3– and physiological performance in seedlings treated with As+Se+P compared with those treated with As+Se. However, supplementation with only PO4 3– (10 μg mL −1 and 20 μg mL −1 ) along with As(V) was less effective in reducing As accumulation compared with As+Se. Seedlings receiving As+Se+P also exhibited lower thiobarbituric acid–reactive substances (TBARS) and electrical conductivity levels compared with both As+Se and As+P. Among all the treatments, the activity of antioxidant enzymes was highest in plants treated with As+Se+P. Hence, the higher antioxidant enzyme activity in As+Se+P along with lower levels of TBARS, H2 O2, and As accumulation are attributed to the competitive reduction in As uptake in the presence of Se(IV) and PO4 3– . Environ Toxicol Chem 2016;35:163–172. © 2015 SETAC